2000
DOI: 10.1200/jco.2000.18.12.2459
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Model for Topotecan Derived From Phase I Clinical Trials

Abstract: A population pharmacokinetic model for total topotecan has been developed that incorporates measures of body size and renal function to predict total clearance. The model can be used prospectively to obtain a revised and validated model that can then be used to design individualized dosing regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 20 publications
5
26
0
1
Order By: Relevance
“…Population pharmacokinetic parameters of topotecan were similar to previously reported parameter estimates obtained using a population approach (Gallo et al, 2000) and a standard two-stage analysis (Wall et al, 1992;van Warmerdam et al, 1995) after singleagent administration of 0.5 -2.0 mg m À2 topotecan in the daily times five schedule. Gallo et al reported a CL of 32 l h À1 and volume of distribution at steady state (V ss ) of 120 l, whereas the current analysis found 29 l h À1 and 80 l, respectively.…”
Section: Discussionsupporting
confidence: 62%
“…Population pharmacokinetic parameters of topotecan were similar to previously reported parameter estimates obtained using a population approach (Gallo et al, 2000) and a standard two-stage analysis (Wall et al, 1992;van Warmerdam et al, 1995) after singleagent administration of 0.5 -2.0 mg m À2 topotecan in the daily times five schedule. Gallo et al reported a CL of 32 l h À1 and volume of distribution at steady state (V ss ) of 120 l, whereas the current analysis found 29 l h À1 and 80 l, respectively.…”
Section: Discussionsupporting
confidence: 62%
“…body weight, serum creatinine, and sex), the accuracy of prediction of topotecan clearance (CL) can be improved only partly (Gallo et al, 2000;Montazeri et al, 2000;Mould et al, 2002). Moreover, clinical protocols are based on repeated daily administrations (usually, 5 consecutive days) giving the opportunity to perform a dose adjustment according to the observed exposure on Day 1.…”
mentioning
confidence: 99%
“…Numerous patients present severe neutropenia as a consequence of a large area under the curve of plasma topotecan concentrations (14). These observations are not surprising regarding the poor correlation between topotecan clearance and BSA (12). In the summary of product characteristics, guidelines for adaptation of topotecan dosage recommend reducing the administered dose by 50% for patients with creatinine clearance ranging between 20 and 40 mL/minute, and to exclude patients with lower values (15).…”
Section: Discussionmentioning
confidence: 99%
“…A proportional error model was used for residual and interpatient variabilities. This model has been previously selected as the best structural pharmacokinetic model for three-population pharmacokinetic analyses (8,12,13).…”
Section: Methodsmentioning
confidence: 99%